The Effect of Using Computer in Teaching English Grammar to the Jordanian University Students: the Passive Voice a Model - Bani Hani, Nedal Awwad (جامعة البحرين - مركز النشر العلمي, 2014)
هدفت هذه الدراسة إلى التحقق من فعالية استخدام برنامج تعليمي محوسب في تحصيل الطلبة الجامعيين في قواعد اللغة الإنجليزية (المبنى للمجهول) في الأردن، تكونت عينة الدراسة من (160) طالبا موزعين بشكل عشوائي إلى مجموعتين إحداهما تجريبية والأخرى ضابطة. استخدم الباحث أداتين وهما: البرنامج التعليمي المحوسب لتعليم المبني للمجهول، واختبار تحصيلي. واستخدم الباحث تحليل التباين لمعرفة أثر استخدام هذا البرنامج على تحصيل الطلبة في المبني للمجهول. وأظهرت نتائج الدراسة وجود فرق ذي دلالة إحصائية على (0.05 α) في تحصيل الطلبة في المبني للمجهول يعزي إلى طريقة التدريس، وكان الاختلاف لمصلحة المجموعة التجريبية التي درست بالحاسوب. وبينت النتائج أيضا وجود فرق ذي دلالة إحصائية على (0.05 α) بين المجموعتين عائد إلى الجنس لمصلحة الذكور، ووجود فرق ذي دلالة إحصائية في تحصيل الطلبة في قواعد اللغة الإنجليزية (المبني للمجهول) في الجامعات الأردنية. This ad hoc study concentrated on investigating the effectiveness of utilizing an instructional computer program of English language on the achievement of university level students in Jordan. The sample of the study consisted of (160) students distributed randomly on two experimental groups and two control groups. The instruments employed in the study were an instructional computer program for teaching the passive voice and an achievement test. An analysis of covariance was utilized to figure out the effect of the instructional program on the students’ achievement in the passive voice. The Endings of the study revealed that: 1. There were statistically significant differences (α < 0.05) between the students' achievement mean scores in the passive voice attributed to the instructional method of teaching. This difference is in favor of the students in the experimental groups 2. There were statistically significant differences (α < 0.05) between the students' achievement mean scores in the passive voice attributed to gender. This difference is in favor of male students. 3. There were statistically significant differences (α < 0.05) between the students' achievement mean scores in grammar attributed to the year of study. This difference is in favor of the (junior & senior) group students. In light of the findings of the study, it was recommended that university instructors use CALL lessons in the teaching of English grammar(Passive Voice).
Keywords: الفعل المبني للمجهول -- قواعد اللغة الانجليزية -- الحاسبات الألكترونية -- طلاب الجامعات الاردنية